Effects of Dietary Promotion Program Guideline of the DASH on Food Consumption Behaviors and Blood Pressure in Patients with Hypertension - Leesagul, Preeya; Juntarawijit, Yuwayong; Puraya, Amaraporn (NU Journal of Nursing and Health Sciences, 2025)
This quasi-experimental research, two-groups pretest-posttest design. The objective aimed to study the effects of the dietary promotion program based on the Dietary Approaches to Stop Hypertension Diet (DASH) on food consumption behaviors and blood pressure levels in patients with hypertension. A total of 60 participants were randomly selected and assigned to the experimental group and control group, consisting of 30 participants in each group. The experimental group received the Dietary Promotion Program Guideline of the DASH developed from Bandura’s self-efficacy theory (Bandura, 1997), while the control group received regular nursing care. This research data collection tools included personal information questionnaire and DASH food consumption behavior questionnaire, which had content validity index (CVI) with validity indices of 0.85 and 0.88, respectively. The food consumption behavior’s reliability, tested using Cronbach's alpha coefficient was 0.84. Statistical analysis included descriptive statistics and t-test. Research findings revealed significant changes following the program implementation: 1) The average score for food consumption behavior of the experimental group showed a statistically significant difference compared to both before the program implementation and the control group (p < .001); 2) The blood pressure levels of the experimental group was statistically significantly lower compared to before the program implementation (p < .001) and lower than the control group. (p <0.05). This study demonstrates that healthcare professionals can effectively use DASH-based dietary promotion program, and utilizing self-efficacy theory, to promote food consumption behavior changes and reduce blood pressure levels of patients with hypertension. However, it is important to note that this study used available food menus in this study area; therefore, adjustments may be needed when implementing the program in different contexts to align with the lifestyle of patients with hypertension residing in other areas.